Sabendo que a-b = 5 e a²-b²= 15, é CORRETO afirmar que:
a) a+b= 1
b)a+b= 2
c)a+b= 3
d)a+b= 4
e)a+b= 5
Soluções para a tarefa
Respondido por
1
Sabemos que
![{a}^{2} - {b}^{2} = (a + b)(a - b) {a}^{2} - {b}^{2} = (a + b)(a - b)](https://tex.z-dn.net/?f=+%7Ba%7D%5E%7B2%7D++-++%7Bb%7D%5E%7B2%7D++%3D+%28a+%2B+b%29%28a+-+b%29)
Se
![{a}^{2} - {b}^{2} = 15 {a}^{2} - {b}^{2} = 15](https://tex.z-dn.net/?f=+%7Ba%7D%5E%7B2%7D++-++%7Bb%7D%5E%7B2%7D++%3D+15)
então
![(a + b)(a - b) = 15 (a + b)(a - b) = 15](https://tex.z-dn.net/?f=%28a+%2B+b%29%28a+-+b%29+%3D+15)
Como a - 5 = 5, segue que:
![(a + b) \times 5 = 15 \\ (a + b) = 3 (a + b) \times 5 = 15 \\ (a + b) = 3](https://tex.z-dn.net/?f=%28a+%2B+b%29+%5Ctimes+5+%3D+15+%5C%5C+%28a+%2B+b%29+%3D+3)
Se
então
Como a - 5 = 5, segue que:
Respondido por
1
a - b = 5 e a² - b² = 15 a + b = ?
a² - b² = (a + b).(a - b) = 15
(a + b) . 5 = 15
a + b = 15 : 5
a + b = 3 (resposta)
opção: c)
Perguntas interessantes
Matemática,
11 meses atrás
Português,
11 meses atrás